FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TAX AVOIDANCE (Studi Empiris Perusahaan Penanam Modal Asing Yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2017) - Yulita Saraswati, 16.05.62.0035; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze and test the effect of profitability, leverage, institutional ownership, company size and sales growth on tax avoidance. This study uses a sample of 90 foreign investment companies listed on the Indonesia Stock Exchange in the period 2015-2017. The sample in this study was obtained by purposive sampling. The type of data used is secondary data. The research data was analyzed by multiple linear regression analysis and data processing was carried out using the SPSS 22.0 for windows software program. The results show that profitability, institutional ownership and sales growth have a significant negative effect on tax avoidance. While leverage has a positive and insignificant effect and firm size has no significant negative effect on tax avoidance.